Ovariectomy-induced bone loss in TNFα and IL6 gene knockout mice is regulated by different mechanisms. (April 2018) - Zhu, Siyi; He, Hongchen; Gao, Chengfei; Luo, Guojing; Xie, Ying; Wang, Haiming; Tian, Li; Chen, Xiang; Yu, Xijie; He, Chengqi
Abstract : We examined the effects of tumor necrosis factor-α (TNFα) and interleukin-6 (IL6) gene knockout in preserving the bone loss induced by ovariectomy (OVX) and the mechanisms involved in bone metabolism. Twenty female wild-type (WT), TNFα -knockout (TNFα −/− ) or IL6- knockout (IL6 −/− ) mice aged 12 weeks were sham-operated (SHAM) or subjected to OVX and killed after 4 weeks. Bone mass and skeletal microarchitecture were determined using micro-CT. Bone marrow stromal cells (BMSCs) from all three groups (WT, TNFα −/− and IL6 −/− ) were induced to differentiate into osteoblasts or osteoclasts and treated with 17-β-estradiol. Bone metabolism was assessed by histological analysis, serum analyses and qRT-PCR. OVX successfully induced a high turnover in all mice, but a repair effect was observed in TNFα −/− and IL6 −/− mice. The ratio of femoral trabecular bone volume to tissue volume, trabecular number and trabecular thickness were significantly decreased in WT mice subjected to OVX, but increased in TNFα −/− mice (1.62, 1.34, 0.27-fold respectively; P < 0.01) and IL6 −/− mice (1.34, 0.80, 0.22-fold respectively; P < 0.01). Furthermore, we observed a 29.6% increase in the trabecular number in TNFα −/− mice when compared to the IL6 −/− mice. Both, TNFα −/− and IL6 −/− BMSCs exhibited decreased numbers of TRAP-positive cells and an increase in ALP-positive cells, with or without E2 treatment ( P < 0.05). While the knockout of TNFα or IL6 significantly upregulated mRNA expressions of osteoblast-related genes ( Runx2 and Col1a1 ) and downregulated osteoclast-related mRNA for TRAP, MMP9 and CTSK in vivo and in vitro, TNFα knockout appeared to have roles beyond IL6 knockout in upregulating Col1a1 mRNA expression and downregulating mRNA expressions of WNT-related genes ( DKK1 and Sost ) and TNF-related activation-induced genes ( TRAF6 ). TNFα seemed to be more potentially invasive in inhibiting bone formation and enhancing TRAF6-mediated osteoclastogenesis than IL6, implying that the regulatory mechanisms of TNFα and IL6 in bone metabolism may be different.